Automated validation system for infineon XMC4500 based software development - Hashim Abdul Razak Bafadhal. (2013)
The requirement of this project is to create a software testing platform for the Infineon XMC4500 device based on the UVP. The UVP consists mainly of a National Instruments PXI machine and the software platform will be constructed based on Labview and FPGA-Xilinx programming and XMC4500 Cortex M4 device programming. The goal of this project is to successfully create this platform to translate the manual test setup for software modules of the XMC4500 into a fully automated test setup.